Dynamic Capabilities In Community-Based MSMEs: How Innovation and Collaboration Enhance Business Performance Through Strategic Agility - Amrullah, Hafizh Irsyad; Rohimat, Asep Maulana (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Community-based Micro, Small, and Medium Enterprises (MSMEs) play an important role in the local economy because they are supported by social networks, collaboration, and a sense of community among business actors. However, MSMEs still face challenges in improving business performance amid a changing environment and dynamic competition. In this context, innovation and collaboration are seen as key factors in strengthening competitiveness, while strategic agility is considered a relevant adaptive capability. This study aims to analyze the influence of innovation and collaboration on MSME business performance and to examine the mediating role of strategic agility in community-based MSMEs at the Ngarsopuro Night Market in Surakarta City. This study uses a quantitative approach with a survey method of 100 respondents who are MSME owners and managers. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results show that innovation and collaboration have a positive and significant effect on MSME business performance. In addition, innovation and collaboration also have a positive and significant effect on strategic agility. However, strategic agility does not have a significant effect on business performance and does not mediate the relationship between innovation and collaboration on business performance. These findings indicate that in community-based MSMEs, improvements in business performance are driven more by innovation and collaboration directly than through the mechanism of strategic agility.